Makna Kuda dalam Tradisi Upacara Pernikahan Suku Alas di Aceh Tenggara - Wawan Dermawan; Puspitawati Puspitawati (Universitas Negeri Medan, 2019)
This study aims to describe the meaning, influence and views of the community in using horses in Alas ethnic tribe marriages in Southeast Aceh. In this study, researchers used a type of qualitative research with a descriptive approach regarding the meaning, influence and views of calm horses in the tradition of the Alas Tribe wedding ceremony in the Southeast Aceh Regency. The results obtained in the study were the use of horses part of the Alas ethnic tribe wedding ceremony originating from the King's tribe pedestal, so that until now still maintaining horses in marriage, the influence of horses in the Alas Tribe wedding tradition in Southeast Aceh was very influential because the tribe used horses as vehicle equipment for the two brides and the views of the outside community of the Alas Ethnic group regarding the tradition of riding horses in the Alas ethnic tribe wedding in Southeast Aceh, that this horse was too excessive and saw social status. The conclusions of the meaning of horses in the traditions of the Ethnic Alas's marriage as strength, intelligence and freedom from that tribe alas still maintain the tradition of using horses in their marriages.